Fresno County Counsel Office Holiday Party - Watkins, Howard::::::::: (1985)
Peggy Smith, Helen Apodaca opening her present, Vickie Stoutingberg; receptionist desk with 24 telephone message slots; double unit telephone system; microphone for paging